2012
DOI: 10.1103/physrevb.85.094412
|View full text |Cite
|
Sign up to set email alerts
|

Flipping magnetization induced by noncollinear ferromagnetic-antiferromagnetic exchange coupling

Abstract: We present a direct observation of a flipping magnetization of a uniform Fe film/wedged-Mn bilayer induced by a biquadratic-type exchange coupling established at the interface. The element-resolved magnetic imaging shows that the Fe film exhibited a flipping of magnetization between the [100] and [010] directions with a periodicity of one monolayer Mn thickness as below a critical temperature. The enhancement of the variation angle with the increase of Mn thickness follows the tendency of the finite-size effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
(56 reference statements)
3
17
0
Order By: Relevance
“…Magnetic ultrathin films were prepared in an ultrahigh vacuum NTU-NSRRC nanomagnetism preparation chamber through thermal evaporation at a base pressure of 2 × 10 −10 Torr. Single crystals of Cu 3 Au(001)(a = 3.75Å) and Cu(001) (a = 3.61Å) with a 0.1 • miscut were used as the substrates, and they were prepared using procedures described in previous reports [10,16,17]. Depending on the objectives of different experiments, either uniform or wedge-shaped Mn/Co bilayers were deposited on the substrates at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Magnetic ultrathin films were prepared in an ultrahigh vacuum NTU-NSRRC nanomagnetism preparation chamber through thermal evaporation at a base pressure of 2 × 10 −10 Torr. Single crystals of Cu 3 Au(001)(a = 3.75Å) and Cu(001) (a = 3.61Å) with a 0.1 • miscut were used as the substrates, and they were prepared using procedures described in previous reports [10,16,17]. Depending on the objectives of different experiments, either uniform or wedge-shaped Mn/Co bilayers were deposited on the substrates at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In magnetologic devices such as the spin valve, the effects of exchange bias fields and coercivity enhancement are extensively used for "pinning" the magnetization of magnetic reference layers [1][2][3][4][5]. Recent studies have reported that antiferromagnetic (AFM) thin films can alter the magnetization direction of the adjacent FM layer, leading to a spin reorientation transition (SRT) that depends on the characteristics or symmetry of the interfacial moments [6][7][8][9][10][11][12]. Such a mechanism can even induce perpendicular magnetization [11][12][13][14], thus enhancing the functionality of AFM thin films.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations